2021
DOI: 10.3389/fpsyg.2020.551806
|View full text |Cite
|
Sign up to set email alerts
|

Temperamental Sensitivities Differentially Linked With Interest, Strain, and Effort Appraisals

Abstract: The present research examined the connections between temperament (punishment sensitivity; interindividual reward sensitivity; intraindividual reward sensitivity), students’ domain- and course-specific motivational appraisals (interest, strain, effort), and performance, in two studies. Study 1 explored the relationships between temperamental sensitivities, motivational appraisals, and task achievement among secondary students (N = 268) in the domain of mathematics, using Exploratory Structural Equation Modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 107 publications
(256 reference statements)
0
3
0
Order By: Relevance
“…CB-SEM Statistical Applications [84,90,99,111] Lisrel (N = 4 studies) [80][81][82][83][91][92][93]97,109,117,119] Amos (N = 11 studies) [94,98,100,[106][107][108]112] Mplus (N = 7 studies)…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…CB-SEM Statistical Applications [84,90,99,111] Lisrel (N = 4 studies) [80][81][82][83][91][92][93]97,109,117,119] Amos (N = 11 studies) [94,98,100,[106][107][108]112] Mplus (N = 7 studies)…”
Section: Studymentioning
confidence: 99%
“…Most of the studies revealed a positive finding regarding the integration of the Mplus tool in SEM analysis. For instance, there is a significant connection between students' cognitive appraisals with enjoyment and mathematics anxiety [106], and punishment sensitivity with psychological strain (motivational appraisals and task achievement) [107]. Moreover, in fourth grade, students who participate in more early numeracy activities at home are more likely to perform well in mathematics [94].…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation